Theoretical Study of the Effects Type of Host’s Crystal on the Lasing Output of High – Power Thin –Disk Laser - Mustafa Muwafaq Muhammed; Mudhir Shihab Ahmed (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
Ytterbium-doped (Y2O3), (Sc2O3) and (YAG) crystals are very important for high-power thindisk lasers. These lasers have shown their ability to operate quasi-three-level materials with high efficiency as well as high thermal conductivity ratio for crystalline hosts. All these reasons have required studying this type of laser. In the present work, the analytical solution was found for the equation of laser output power, pumping threshold power, and efficiency of a quasi-three-level thin disk laser. The numerical solution of these equations was also found through the Matlab program at the fundamental transverse mode, at a temperature of 299K0 and with high pumping capabilities in order to know the effect of the type of crystal host (YAG, Sc2O3,Lu2O3) on the laser production of this design and thermal effect when operating continuously. We found out that the crystal host (Lu2O3) was the best type of these hosts in obtaining the highest laser output power and efficiency at all values of pumping power